Response of Some Bread Wheat Genotypes (Triticum aestivum L.) to Salinity at Early Growth Stage - Maqsuda Q. Muhammad; Mohammed Q. Khursheed; Sirwa A. Qadir (Zanco Journal of Pure and Applied Sciences, 2023)
This study aimed to detect the salinity harsh influence on germination of Triticum aestivum L. seeds, seedling growth and some physiological defense mechanisms to determine the salt- tolerant genotype. The study conducted as a completely randomized design with 3 replicates for each treatment. Four bread wheat genotypes; Hawler- 2, Azady, Adana, Rabeae were subjected to two irrigation patterns; tape water (control) and 100 mM NaCl (salt stress). The highest percent of germination; 46.77 recorded by Rabeaa genotype. Meanwhile Azady and Rabeaa had highest mean germination time (MGT); 16.71 and 16.03 respectively. Longest root was exhibited by Adena;10.50 cm. while longest shoot represented by Hawler-2; 16.40 cm. Highest dry weight of root was 1.01 g. Root: shoot ratio; 1.63 exhibited by Rabeaa. Hawler- 2 showed minimum chlorophyll a; 0.90 mg/ g. Lowest chlorophyll b and total content observed in Adena; 2.18 and 2.3 mg g-1 respectively. Azady and Rabeaa recorded higher MSI%; 43.3 and 43 % respectively as compared to others. Rabeaa recorded highest water content, proline and sugar content; 22.7, 0.31 and 11.56 mg g-1. Therefore, it could suggest that Rabea and Azady can be successfully grown under 100 mM NaCl saline condition.